Intellectual structure and evolution of accounting conservatism research: Past trends and future research suggestions - Umair Saeed Bhutta; Jéssica Nunes Martins; Mário Nuno Mata; Ali Raza; Rui Miguel Dantas; Anabela Batista Correia; Muhammad Rafiq (International Journal of Financial Studies, 2021)
Accounting conservatism (AC) is one of the components of financial reporting, and has been widely studied by academicians to identify its impact on information quality. Scholars in accounting have started to explore how AC is related to different fundamental functional areas of organizations. The interest of the scholars has resulted in an increasing number of publications in this field. In this study, we examined 408 indexed publications related to AC. This work's objectives include analyzing the regional distribution, size, and evolution of this knowledge base by identifying key authors, documents, and journals while exploring current literature, scholarly structure, and highlighting contemporary trends. The findings of the study concluded that most of the studies are conducted in developed nations contexts. However, there are still areas that need further exploration to obtain more profound insights on the subject. This bibliometric review inspires a new generation of researchers on the topic by giving them an overview of the past studies related to AC.
Keywords: 330; accounting conservatism; bibliometric analysis; co-citation; bibliographic coupling; co-occurrence